A community-based study of dental fluorosis in rural children (6–12 years) from an aspirational district in Karnataka, India - U. Venkateswara Prasad; Phaniraj Vastrad; Chandan N.; Manish J. Barvaliya; Rahul Kirte; Rahul Kirte; Sabarinath R.; Suman K. Ray; Ravichandran B.; Tapas Chakma; Manoj V. Murhekar; Subarna Roy; et al. (Frontiers in Public Health, 2023)
ObjectivesThe present study was planned to estimate the prevalence of dental fluorosis in 6–12 years of children and its association with various drinking water sources, water, and urine fluoride levels among the subset of children under the umbrella of a larger study to address iodine deficiency disorders and iron deficiency anemia in 17 villages of Manvi and Devadurga talukas of Raichur district of Karnataka.MethodsAnalysis of subset of data and urine samples of children under the umbrella of a larger cross-sectional community-based study was conducted in 17 villages of Manvi and Devadurga taluks of Raichur district. House to house survey was carried out to collect data using a semi-structured questionnaire in ODK software. Demographic details, source of drinking water, clinical assessment of dental fluorosis, and height and weight measurements were performed by trained staff. Urine and water samples were collected for fluoride level estimation. The overall prevalence of dental fluorosis and its severity-wise prevalence were estimated. Association between dental fluorosis and age, gender, type of diet, source of drinking water, height for age, BMI for age, water fluoride level, and urine fluoride level were carried out using logistic regression analysis.ResultsThe prevalence of dental fluorosis was 46.0%. Mild, moderate, and severe dental fluorosis was found in 37.9, 7.8, and 0.3% of children. With the increasing age of participants, the odds of dental fluorosis were found to increase by 2–4 folds. The odds of having dental fluorosis were significantly increased with increasing water fluoride levels of 3 to 5 ppm [AOR = 3.147 (1.585–6.248); P = 0.001] in comparison with water fluoride levels of < 1 ppm. The similar trend was found with urine fluoride level > 4 ppm [AOR = 3.607 (1.861–6.990); P < 0.001]. As compared to river water, other sources of drinking water were significantly associated with higher odds of dental fluorosis.ConclusionsPrevalence of dental fluorosis was high in 6 to 12 years due to overexposure of fluoride from drinking water. High water and urine fluoride levels in children indicate the chronic exposure to fluoride and suggest that the population is at high risk of developing chronic fluorosis.